Maritime Diplomacy as Indonesia's Strategic Pillar in Addressing South China Sea Threats through a Contemporary Approach - Baqi Zaenulhaq Alfarizi; Arry Bainus; Arif Sudirman (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The South China Sea is a strategic region filled with complex geopolitical and geostrategic interests, particularly for Indonesia, which faces sovereignty violations in its Exclusive Economic Zone (EEZ) in the North Natuna Sea. In addressing these threats, Indonesia has positioned maritime diplomacy as a strategic pillar that integrates foreign policy instruments, defense, and international law supremacy. This study aims to analyze Indonesia’s maritime diplomacy role in responding to threats in the South China Sea using a qualitative-descriptive approach based on literature studies and document analysis. The findings indicate that Indonesia’s maritime diplomacy is carried out through bilateral and multilateral diplomacy, naval diplomacy, coast guard diplomacy, and the enforcement of international law based on UNCLOS 1982. Despite facing various internal and external challenges, Indonesia's maritime diplomacy has proven effective in maintaining regional stability, strengthening Indonesia's legal position internationally, and managing conflict dynamics peacefully. This study recommends strengthening national maritime capacity, optimizing inter-agency coordination, and enhancing multilateral diplomacy to address future complex threats.